Maternal resources for care are associated with child growth and early childhood development in Bangladesh and Vietnam - Basnet, Sulochana; Frongillo, Edward A.; Nguyen, Phuong Hong; Moore, Spencer; Arabi, Mandana (Wiley, 2022)
Background: Suboptimal child growth and development are significant problems in low- and middle-income countries. Maternal resources for care may help to improve growth and development. This study examined the association of maternal resources for care on child length, motor development and language development of children 12–23.9 months old. Methods: We used baseline data from the Alive & Thrive household surveys collected in Bangladesh (n = 803) and Vietnam (n = 635). Resources for care were represented by maternal education, knowledge, height, well-nourishment, mental well-being, decision-making, employment, support in chores and perceived support. The regression analyses were adjusted for household wealth and other covariates on households, children and parents and accounted for geographical clustering. Results: Maternal height (Bangladesh β = 0.150 p < 0.001, Vietnam β = 0.156 p < 0.001), well-nourishment (Vietnam β = 0.882 p = 0.007) and mental well-being (Bangladesh β = 0.0649 p = 0.008, Vietnam β = 0.0742 p = 0.039) were associated with child length. Well-nourishment (Vietnam β = 0.670 p = 0.042) and support in chores (Bangladesh β = 0.0983 p = 0.021) were associated with child motor development. Mental well-being (Vietnam β = 0.0735 p = 0.013), decision-making autonomy (Bangladesh β = 0.0886 p = 0.029) and perceived support (Vietnam β = 0.445 p = 0.003) were associated with child language development. Conclusion: Maternal height, well-nourishment, mental well-being, decision-making, support in chores and perceived social support were associated with child outcomes. Interventions that help to improve resources among mothers have potential to foster child growth and development.